Groups with the Infinite Non-Quasicentral Nodal Subgroup - Ludovit Tomanek; Anna Tomankova (Communications - Scientific letters of the University of Zilina, 2014)
We present some properties of the groups with the infinite non-quasicentral periodic nodal subgroup. Our main results are formulated in Theorem 1, 2 and Theorem 3, 4. 2000 Mathematics Subject Classification: 20F22, 20F25